Public Opinion Regarding Information on Porcine-Contained Medications - Anindhita Paramita Wibowo; Yoni Fuadah Syukriani; Teguh Marfen Djajakusumah (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Drugs are biological products, a single or combination of active and additives components. Some additional components are derived from porcine, a substance that is haraam for Muslims. Patient’s rights, such as medication information, are substantial in decision-making process. Medical decision-making in the Eastern culture is not only the patient’s affair, but also family’s interest. This study aimed to determine the public opinion on that matter. Methods: This study was conducted in October–November 2014 using qualitative methods. Data collection was performed in the District of Jatinangor, Sumedang Regency by using the purposive sampling method. Six respondents were selected. Data were collected through in-depth interview techniques and were analyzed using content analysis technique.Results: There were 3 main responses regarding the respondent’s opinions. First, respondents showed several attitudes toward drugs in general and also several attitudes toward porcine-contained drugs. Respondents showed concern for the medications used and wished either to be informed or not about the prohibited substance in the drugs. The decision-making process of respondents was performed by each individual or family, with the guidance of religious scholars. In a doctor-patient relationship, the doctors should be more active in providing information on the medications and the opportunity for patients to choose drugs. Respondents also had a high dependency to the physicians in making medical decisions.Conclusions: Public opinion on patient’s rights regarding porcine-contained drugs shows the people’s attitude towards drugs in general and porcine-contained drugs in particular, the decision-making process and the relationship between physicians and patients.